1979
DOI: 10.1159/000468400
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucose Tolerance in Long-Term Lithium-Treated Patients

Abstract: The oral glucose tolerance test (oGTT) was performed twice in patients under long-term lithium treatment. Blood glucose and plasma insulin were determined. The oGTT results were evaluated by three criteria (Köbberling-Creutzfeldt, WHO, and Epidemiological Study Group of the European Diabetes Association) and were compared to two representative reference studies from normal populations. The frequency of impaired glucose tolerance in the patients was three times higher than expected on the basis of the studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The reported prevalence of obesity in BD varies from 1.4 to 55.4 % (Kim et al 2009 ;McIntyre et al 2010c ;Kemp et al 2010Kemp et al , 2013Guo et al 2006 ;Carney and Jones 2006 ;Krishnan 2005 ;Salvi et al 2008 ;Weber et al 2011 ;Petry et al 2008 ;McIntyre et al 2007a ;McElroy et al 2002McElroy et al , 2004McElroy et al , 2013Elmslie et al 2000Elmslie et al , 2001Mather et al 2009 ;Maina et al 2008 ;Fagiolini et al 2002 ;Calkin Chwastiak et al 2011 ;Muller-Oerlinghausen et al 1979 ;Fiedorowicz et al 2008Fiedorowicz et al , 2011Birkenaes et al 2007 ), and this high variability of results makes conclusions diffi cult. Reversely, in morbidly obese patients, BD is diagnosed at a rate of 2.8-11 % (Black et al 1992 ;Britz et al 2000 ;Simon et al 2006 ).…”
Section: Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of obesity in BD varies from 1.4 to 55.4 % (Kim et al 2009 ;McIntyre et al 2010c ;Kemp et al 2010Kemp et al , 2013Guo et al 2006 ;Carney and Jones 2006 ;Krishnan 2005 ;Salvi et al 2008 ;Weber et al 2011 ;Petry et al 2008 ;McIntyre et al 2007a ;McElroy et al 2002McElroy et al , 2004McElroy et al , 2013Elmslie et al 2000Elmslie et al , 2001Mather et al 2009 ;Maina et al 2008 ;Fagiolini et al 2002 ;Calkin Chwastiak et al 2011 ;Muller-Oerlinghausen et al 1979 ;Fiedorowicz et al 2008Fiedorowicz et al , 2011Birkenaes et al 2007 ), and this high variability of results makes conclusions diffi cult. Reversely, in morbidly obese patients, BD is diagnosed at a rate of 2.8-11 % (Black et al 1992 ;Britz et al 2000 ;Simon et al 2006 ).…”
Section: Obesitymentioning
confidence: 99%
“…Lithium (Vendsborg et al 1976 ;Sachs et al 2006 ) and valproate (Dinesen et al 1984 ;Pylvanen et al 2002 ;Swann 2001 ) can cause weight gain. It has been reported that patients on lithium gain weight in contrast to patients under lamotrigine Muller-Oerlinghausen et al 1979 ;Atmaca et al 2002 ;Vendsborg et al 1976 ) and weight gain during lithium treatment has shown to lead to poor adherence (Gitlin et al 1989 ). Treatment with antipsychotics and especially with those belonging to the second generation has also been related to weight gain (Henderson et al 2000 ;Simpson 2005 ;Volavka et al 2002 ;Zipursky et al 2005 ;Nasrallah 2003 ).…”
Section: Obesitymentioning
confidence: 99%